Applying Semigroup Property of Enhanced Chebyshev Polynomials to Anonymous Authentication Protocol. (23rd September 2012) - Lai, Hong; Xiao, Jinghua; Li, Lixiang; Yang, Yixian
Abstract : We apply semigroup property of enhanced Chebyshev polynomials to present an anonymous authentication protocol. This paper aims at improving security and reducing computational and storage overhead. The proposed scheme not only has much lower computational complexity and cost in the initialization phase but also allows the users to choose their passwords freely. Moreover, it can provide revocation of lost or stolen smart card, which can resist man-in-the-middle attack and off-line dictionary attack together with various known attacks.